Illuminating GPCR Signaling by Cryo-EM. Issue 8 (August 2018) - Safdari, Haaris Ahsan; Pandey, Shubhi; Shukla, Arun K.; Dutta, Somnath
Abstract : The wave of resolution revolution in cryo-EM has touched, and made a significant impact on, the structural biology of GPCRs. High-resolution structures of several GPCR-G-protein complexes are now determined by cryo-EM and they illuminate fine structural details of this central macromolecular complex involved in cellular signaling.